Conjunctivitis among Rural and Urban School Children in Erbil Governorate/ Iraq - Fisal Shakir Agha, Nabaz (Diyala Journal of Medicine, 2020)
Background: In children conjunctivitis is the most widespread ocular surface disease. It is referred to any inflammatory condition of the conjunctiva. Conjunctivitis was the most common associated comorbidities that had an influence on the health of children. Objective: To compare the prevalence of allergic and infective conjunctivitis among school children in the rural & urban Regions of Erbil Governorate / Iraq. Patients and Methods: A cross-sectional study was performed from the 1st Sep 2018 – end of May 2019 in primary schools in the rural area of Makhmur district and urban districts in Erbil Governorate .From every suspected case of clinically conjunctivitis, a sample for bacterial culture was gained by winding a thin cotton micro swab moistened in brain heart infusion broth over the lower fornix of the conjunctival sac.After culturing on blood, chocolate, and MacConkey agars, the colonies were specified and identified by using Gram staining technique, morphological, biochemical & Analytical Profile Index (API) tests.Allergic conjunctivitis was diagnosed clinically. The Kurdish & Arabic versions of International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire were used. MS excel package and SPSS 20 software was used for analysis. Results: The total numbers of urban and rural School children who had shared in this study were 1129 and 1093 respectively. The prevalence of infective conjunctivitis in both urban & rural children was as such: 127(11.2%) & 211(19.3%).The rates of positive culture in both were: urban 69, 54.3%; rural 143, 67.8 %( p≤ 0.01). Staphylococcus aureus was the most common pathogen isolated, urban: 37(53.6%) rural: 79(55.2%).Infective conjunctivitis was distributed significantly in young ages and in male students (p≤0.05).Regarding allergic conjunctivitis: the prevalence of allergic conjunctivitis were: urban 247(21.9%), rural 81(7.4%).Allergic conjunctivitis was more distributed in older ages and male children, but this was not-significant .itching was complained by all student. Conclusion: Infectious conjunctivitis among rural school children is still a major public health problem. While higher percentage of allergic conjunctivitis among urban school children was noted.